A narrative account of third space technology enhanced learning and teaching roles working in Australian higher education - Kate Mitchell; Kashmira Dave; Meredith Hinze; Alex Tsirgialos (Journal of Learning Development in Higher Education)
We provide a collaborative autoethnographic narrative account (Poulos, 2021) of our experiences as practitioners working in overlapping, related Technology Enhanced Learning (TEL) roles (academic developer, learning designer, educational technologist) in Australian universities. Despite wide ranging demand for our roles, particularly during and post COVID pandemic (Bellaby and Sankey, 2020; Baré et al., 2021) these ‘third space’ roles (Whitchurch 2008; 2013) are often not well understood (Mitchell et al., 2017; Altena et al., 2019). Such roles may experience challenges in credibility and visibility (Fyffe, 2018), relationship-building (Mitchell et al., 2017), and limitations for career progression (Slade et al., 2019). We provide a selection of our accounts related specifically to key tensions for third space TEL roles in building collaborative relationships and what these contradictions in practice can mean for productivity, morale, wellbeing, career progression and identity formation.